Impact of health sector reforms on hospital productivity in Turkey: Malmquist index approach. Issue 2 (11th June 2018) - Mollahaliloglu, Saleh; Kavuncubasi, Sahin; Yilmaz, Fikriye; Younis, Mustafa Z.; Simsek, Fatih; Kostak, Mustafa; Yildirim, Selami; Nwagwu, Emeka
Abstract : Purpose: Turkish Ministry of Health (MoH) has Health Transformation Program (HTP). The purpose of this program has been to modify the structure of the current system in order to enhance health system productivity, quality, and access in the Turkish health system. The paper aims to discuss these issues. Design/methodology/approach: To measure the productivity, a data envelopment analysis-based Malmquist index approach was employed. Findings: Results showed that the overall HTP have had a considerable positive impact on the productivity of general hospitals. Research limitations/implications: The limitation is the availability of some data that might not be collected or reported to the MoH in Turkey. Practical implications: This research's findings will have an impact on reforming the health care system in Turkey to be competitive and efficient as possible. Social implications: The research will have implication on reducing cost and provide value to the Turkish population. Originality/value: This is one of the very few articles that targeted the efficiency of hospital system in Turkey.